Towards smoke-free rental cars: an evaluation of voluntary smoking restrictions in California. Issue 3 (15th February 2012) - Matt, Georg E; Fortmann, Addie L; Quintana, Penelope J E; Zakarian, Joy M; Romero, Romina A; Chatfield, Dale A; Hoh, Eunha; Hovell, Melbourne F
Abstract : Introduction: Some car rental companies in California and other states in the USA have established non-smoking policies for their vehicles. This study examined the effectiveness of these policies in maintaining smoke-free rental cars. Methods: A stratified random sample of 250 cars (non-smoker, smoker and unknown designation) was examined in San Diego County, California, USA. Dust, surfaces and the air of each vehicle cabin were sampled and analysed for residual tobacco smoke pollutants (also known as thirdhand smoke (THS)), and each car was inspected for visual and olfactory signs of tobacco use. Customer service representatives were informally interviewed about smoking policies. Findings: A majority of putative non-smoker cars had nicotine in dust, on surfaces, in air and other signs of tobacco use. Independent of a car's smoking status, older and higher mileage cars had higher levels of THS pollution in dust and on surfaces (p<0.05), indicating that pollutants accumulated over time. Compared with smoker cars, non-smoker cars had lower levels of nicotine on surfaces (p<0.01) and in dust (p<0.05) and lower levels of nicotine (p<0.05) and 3-ethynylpyridine (p<0.05) in the air. Non-smoking signage in cars was associated with lower levels of THS pollutants in dust and air (p<0.05). Conclusions: Existing policies and practices were successful in lowering THS pollution levels in non-smoker cars compared with smoker cars. However, policies failed in providing smoke-free rental cars; THS levels were not as low as those found in private cars of non-smokers with in-car smoking bans. Major obstacles include inconsistent communication with customers and the lack of routine monitoring and enforcement strategies. Strengthening policies and their implementation would allow car rental companies to reduce costs, better serve their customers and make a constructive contribution to tobacco control efforts.